1999
DOI: 10.1016/s0029-7844(99)00324-5
|View full text |Cite
|
Sign up to set email alerts
|

Preterm labor: placental pathology and clinical correlation

Abstract: Preterm labor resulting from infection or ischemia is associated with a higher perinatal complication rate than idiopathic preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 15 publications
2
39
0
5
Order By: Relevance
“…Regardless of these inconsistencies, these few reports implicate that PGE2 may play a role in regulating trophoblast cellular function and that dysregulation of PGE2 production at the gestational compartment may affect trophoblast invasion and migration that are critical for proper placentation (Pijnenborg et al , 1983; Pijnenborg et al , 1980). Moreover, dysregulation of PGE2 production within the gestational compartment has been linked to adverse birth outcomes such as intrauterine growth restriction, preeclampsia and preterm birth (Germain et al , 1999; Ness and Sibai, 2006). Because improper placentation is associated with adverse obstetrical complications (Brosens, 1977; Hustin et al , 1983; Kim et al , 2003), further investigation will be needed to ascertain the potential relevance of BDE-47 stimulation of PGE2 on trophoblast invasion and placental function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of these inconsistencies, these few reports implicate that PGE2 may play a role in regulating trophoblast cellular function and that dysregulation of PGE2 production at the gestational compartment may affect trophoblast invasion and migration that are critical for proper placentation (Pijnenborg et al , 1983; Pijnenborg et al , 1980). Moreover, dysregulation of PGE2 production within the gestational compartment has been linked to adverse birth outcomes such as intrauterine growth restriction, preeclampsia and preterm birth (Germain et al , 1999; Ness and Sibai, 2006). Because improper placentation is associated with adverse obstetrical complications (Brosens, 1977; Hustin et al , 1983; Kim et al , 2003), further investigation will be needed to ascertain the potential relevance of BDE-47 stimulation of PGE2 on trophoblast invasion and placental function.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, prostaglandin E2 (PGE2) is one of the most extensively studied prostaglandins, and has been shown to play critical roles in processes required in successful pregnancy, for example, implantation (Psychoyos et al , 1995; Yee et al , 1993), immunoprotection of the semiallogenic conceptus (Parhar et al , 1988), and parturition (Keelan et al , 2003). Dysregulation of PGE2 production within the gestational compartment has been linked to adverse birth outcomes such as intrauterine growth restriction, preeclampsia and preterm birth (Germain et al , 1999; Ness and Sibai, 2006). Although it is not fully understood how dysregulated prostaglandin pathways lead to these adverse impacts, it is suggested that PGE2 regulates trophoblast cellular functions that are critical for successful placentation (Biondi et al , 2006; Horita et al , 2007a; Nicola et al , 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Our current findings of higher blood pressure, higher lipids, and higher IMT are consistent with postpartum studies of women following pregnancies complicated by preeclampsia. 32,33 A third of normotensive PTBs are associated with placental abnormalities commonly found in preeclampsia, 34,35 suggesting some shared pathophysiology between these pregnancy complications that may be related to excess maternal CVD risk. In contrast to our current findings, Fraser et al recently reported that higher blood pressure assessed 18 years after preterm vs. term births in the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort in England was explained by hypertension in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It could differentiate between the very high risk which needs close fetal testing or even a more aggressive approach for intervention, versus a lower-risk population which does not need that intensive monitoring, as it is currently being used. An additional advantage is that this new method may be able to characterize changes in the fetoplacental blood flow and may provide additional information about the pathophysiology of conditions like, for example, preterm labor which might be associated with placental insufficiency [26]. Ongoing studies are now aimed at identifying obstetrical subgroups that may benefit the most from this new approach.…”
Section: Discussionmentioning
confidence: 99%